Remote Patient Healthcare surveillance system based real-time vital signs - Alsahi, Qunoot N.; Marhoon, Ali F.; Hamad, Ali H. (Al-Khwarizmi Engineering Journal, 2020)
Today many people suffering from health problems like dysfunction in lungs and cardiac. These problems often require surveillance and follow up to save a patient’s health, besides control diseases before progression. For that, this work has been proposed to design and developed a remote patient surveillance system, which deals with 4 medical signs (temperature, SPO2, heart rate, and Electrocardiogram ECG. An adaptive filter has been used to remove any noise from the signal, also, a simple and fast search algorithm has been designed to find the features of ECG signal such as Q,R,S, and T waves. The system performs analysis for medical signs that are used to detected abnormal values. Besides, it sends data to the Base-Station with a data block (ECG signals) that contains the problem. In addition, it generates an alarm to the physicians via ringing up mobile and SMS to overcome the internet disconnected. Also, the system has been designed to achieve precision, low cost, and low energy consumption. Three types of sensors has been used in this work, ECG, SPo2, and temperature sensors. Also, a sim800L GSM module has been used for communications, the main controller in this work is ESP32 unit.